2016
DOI: 10.1155/2016/4518281
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Interaction between Different Flavonoids and PDIA3

Abstract: Flavonoids, plant secondary metabolites present in fruits, vegetables, and products such as tea and red wine, show antioxidant, anti-inflammatory, antithrombotic, antiviral, and antitumor activity. PDIA3 is a member of the protein disulfide isomerase family mainly involved in the correct folding of newly synthetized glycoproteins. PDIA3 is associated with different human pathologies such as cancer, prion disorders, Alzheimer's disease, and Parkinson's diseases and it has the potential to be a pharmacological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
(58 reference statements)
0
9
1
Order By: Relevance
“…These limits could be overcome by simultaneously using multiple evaluation criteria for oxidative stress. A redox state index was therefore proposed, the OXY-SCORE, [ 122 , 123 , 124 ], a global index of oxidative stress, which results from the integrated evaluation of a series of pro-oxidant and anti-oxidant biomarkers.…”
Section: Available Methods To Assess Oxidative Stress In Clinical mentioning
confidence: 99%
“…These limits could be overcome by simultaneously using multiple evaluation criteria for oxidative stress. A redox state index was therefore proposed, the OXY-SCORE, [ 122 , 123 , 124 ], a global index of oxidative stress, which results from the integrated evaluation of a series of pro-oxidant and anti-oxidant biomarkers.…”
Section: Available Methods To Assess Oxidative Stress In Clinical mentioning
confidence: 99%
“…Interestingly, morin and kaempferol differ in the specific position of a single hydroxyl group. Retusin, a flavonol characterized by the presence of a methoxyl group in four positions (on the A, B and C rings) was then tested and also observed to inhibit phage development [ 39 ]. As wine contains considerable amounts of flavonol glycosides, we chose to test one of the main compounds, namely, quercetin-3- O -glucuronide.…”
Section: Resultsmentioning
confidence: 99%
“…PDIA3 has been thought to participate in the mechanisms of cell protection against oxidative stress (Giamogante et. al, ). Several studies have demonstrated that dietary prebiotics and its by‐products can affect expression of proteins involved in the antioxidant activity (LepczyƄski et.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, animals fed with E1 diet showed decreased expression of medullary PDIA4. PDIA3 has been thought to participate in the mechanisms of cell protection against oxidative stress (Giamogante et. al, 2016).…”
Section: Discussionmentioning
confidence: 99%